Between market failure, policy failure and "community failure": property rights, crop-livestock conflicts and the adoption of sustainable land use practices in the dry zone of Sri Lanka - Birner, Regina; Gunaweera, Hasantha (International Food Policy Research Institute, 2001)
Using the case of the semi-arid zone of Southern Sri Lanka as an example, the paper shows that crop damages caused by grazing livestock can constitute an important obstacle to the adoption of available technologies for more sustainable land use. The paper considers crop damages as an externality problem and shows that the classical solutions to externalities - the neo-liberal, the interventionist solution and the communitarian solution - cannot be applied in the Sri Lankan case due to market failure, government failure and "community failure." The paper discusses collective action and bargaining between organized interest groups as an alternative solution and analyses the conditions which make such a solution work. The paper concludes that - in the Sri Lankan case - a decentralized system of government, a preferential voting system creating incentives for politicians, an institutionalized negotiation platform, and the facilitating role of intermediaries favored this solution.